REALISTIC ASSET CREATION WITH ADOBE SUBSTANCE 3D create materials, textures, filters, and 3D models using substance 3D painter, designer and Stager - Shah, Zeeshan Jawed (PACKT PUBLISHING LIMITED, 2023)
Gain extensive, practical knowledge of 3D design with Adobe Substance 3D and learn to build a comprehensive portfolio of work with this interactive book Key Features Find out how to use Adobe Substance 3D swiftly and with little prior knowledge Use a variety of interactive projects to get familiar with the fundamentals Create better career prospects for yourself by mastering 3D design with a single comprehensive guide Book Description Adobe Substance 3D is a comprehensive suite complete with everything an artist needs to create stunning 3D digital materials. Getting a grip on the ecosystem of apps can be challenging for beginners, which is where Realistic Asset Creation with Adobe Substance 3D comes in! This practical guide doesn't bombard you with reams of textual information. Instead, you get an interactive, project-based book that'll help you gain sound knowledge of Adobe Substance 3D and set you on the right path toward a career in 3D design. You'll start off with the rudiments of Adobe Substance 3D Painter, which will enable you to acquire the skills needed to work with layers, masks, shelves, textures, and more. Next, you'll move on to Adobe Substance 3D Designer and become well-acquainted with this node-based design tool as you progress through the chapters. The final section is devoted to Adobe Substance 3D Stager, which teaches you to build complex 3D scenes and visualize your edits in real time. By the end of this Adobe book, you'll have gained a solid understanding of Adobe Substance 3D and developed the skills to build a comprehensive portfolio of work, setting you up for a lucrative career in 3D design. What you will learn Discover Substance 3D Painter, Designer, and Stager through easy projects Assemble 3D scenes and set up assets, materials, lights, and cameras Explore the innovative 3D assets library and learn how to digitize your 3D assets Texture your 3D assets with advanced brushes and Smart Materials Use and blend a variety of nodes in Adobe Substance 3D Designer Create and export materials using Adobe Substance 3D Sampler Who this book is for This book is for game designers, 3D generalists, and design students. If you're looking to get started in your 3D career or planning to join 3D generation, then you'll find this book useful. The book assumes very little to no 3D design knowledge. A bit of understanding of the history, functionality, and purpose of the Adobe Substance 3D package is presumed but is not mandatory; however, you must know how to work with Adobe Photoshop.